Soil Characteristics on Sustainable Food Agriculture Land (LP2B) In Sawerigadi Sub-District, Muna Barat Regency - Wa Embe; A. Asriani (Agrotech Journal, 2021)
The research was conducted in Sawerigadi Subdistrict on Sustainable Food Agricultural Land (LP2B) consisting of five profiles. The research objectives were to determine soil characteristics in physics, chemistry, biology, and to determine the level of soil fertility on it. The research method that is; 1) Land Survey, 2) Research implementation includes the both preparation stage and data collection stage (field implementation), 3) Soil analysis includes analysis of physics, chemistry and biology. Observation and carried out soil sampling were by making soil profiles at the each point. The results of the observation physical properties from the five profiles were almost the same, which had a reddish yellow to brownish yellow color with the texture of loam, clay, clay loam to silty clay. Soil structure is angular blocky and rounded blocky and has a slightly sticky to very sticky consistency. The results of laboratory analysis of the five research profiles have slightly acidic to neutral pH, very low to low C-Organic and NTotal, very low to moderate CEC, very low to very high alkali saturation, P-available is low to very high, K-available is low to moderate, and very low to high base cations (Mg, Ca, Na, K). The value from the results of laboratory analysis of the five profiles at each layer tended to decrease with soil depth. The biological characteristics of the five research profiles are related to macro and micro activity of soil fauna, a little to a lot, the existence of macro and micro activity of soil fauna depending on vegetation conditions on the soil surface. The soil fertility level of the five research profile is in the low to medium category